Quaternary Ostracoda as Palaeoenvironmental Proxies - Frenzel, P. (My University, 2017)
Ostracoda are minute crustaceans with a calcified, two-valved carapace. They are a classical group of micropalaeontology because of their long and rich record in earth history going back to Ordovician times. The presentation introduces into morphology, ecology and distribution of this group and demonstrates methods of its use in palaeoenvironmental analysis. Examples of application in coastal geology, palaeoclimatology, environmental micropalaeontology and geoarchaeology are given
Seminar
Keywords: Ostracoda; morphology; ecology; palaeoenvironmental analysis